DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF DAN HASIL BELAJAR SISWA PADA KONSEP KEANEKARAGAMAN HAYATI - IZZATIN NISA'; IIN BAROROH MA’ARIF; OSPA PEA YUANITA MEISHANTI (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2020)
ABSTRACT This research is a Classroom Action Research (CAR) that aims to determine the effect of the application of the Discovery Learning learning model to the improvement of creative thinking abilities and learning outcomes of class X MIA students on biodiversity material. Because in class X MIA has not fully implemented a learning model that invites students to think creatively so that student learning outcomes have not yet reached indicators of achievement. This research was conducted in 2 cycles, each stage of the cycle consisting of four stages namely planning, implementing, observing, and reflecting. From the results of this study it can be seen the percentage of mastery of creative thinking and student learning outcomes from cycle I and cycle II. In the first cycle, students' creative thinking ability increased reaching 52.4%. Furthermore, in the second cycle, students' creative thinking skills increased, reaching 82.3%. While learning outcomes in the first cycle the average value of students increased by 19.5 from 41.2 in the pre-test increased to 60.7 in the post-test. Then in cycle II the average value of students increased by 30 from 49.41 in the pre-test to 79.41 in the post-test. From these explanations it can be said that the application of discovery learning learning models to improve creative thinking abilities and student learning outcomes in biodiversity material is said to be successful because it can exceed the predetermined achievement indicator targets ie average grade value ≥ 75. KEYWORD: Creative Thinking, Discovery Learning, Learning Outcomes, CAR. ABSTRAK Penelitian ini merupakan penelitian Tindakan Kelas (PTK) yang bertujuan untuk mengetahui pengaruh penerapan model pembelajaran Discovery Learning terhadap peningkatan kemampuan berfikir kreatif dan hasil belajar siswa kelas X MIA materi keanekaragaman hayati. Karena di kelas X MIA belum sepenuhnya menerapkan model pembelajaran yang mengajak siswa untuk berpikir kreatif sehingga hasil belajar siswa belum mencapai indikator pencapaian. Penelitian ini dilaksanakan dalam 2 siklus, tiap tahapan siklusnya terdiri dari empat tahap yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Dari hasil penelitian ini dapat diketahui persentase ketuntasan berfikir kreatif dan hasil belajar siswa dari siklus I dan siklus II. Pada siklus I, kemampuan berpikir kreatif siswa meningkat mencapai 52,4%. Selanjutnya, pada siklus II kemampuan berpikir kreatif siswa semakin meningkat mencapai 82,3%. Sedangkan hasil belajar pada siklus I nilai rata-rata siswa meningkat sebesar 19,5 dari semula 41,2 pada pre-test meningkat menjadi 60,7 pada post-test. Kemudian pada siklus II nilai rata-rata siswa meningkat sebesar 30 dari 49,41 pada pre-test menjadi 79,41 pada post-test. Dari penjelasan tersebut dapat dikatakan bahwa penerapan model pembelajaran discovery learning untuk meningkatkan kemampuan berfikir kreatif dan hasil belajar siswa materi keanekaragaman hayati dikatakan berhasil karena dapat melampaui target indikator ketercapaian yang ditetapkan sebelumnya yaitu rata-rata nilai kelas ≥ 75. Kata Kunci: Berfikir Kreatif, Discovery Learning, Hasil Belajar, PTK.